New age constraints for the limit of the British–Irish Ice Sheet on the Isles of Scilly. (January 2017) - Smedley, R. K.; Scourse, J. D.; Small, D.; Hiemstra, J. F.; Duller, G. A. T.; Bateman, M. D.; Burke, M. J.; Chiverrell, R. C.; Clark, C. D.; Davies, S. M.; Fabel, D.; Gheorghiu, D. M.; et al.
ABSTRACT: The southernmost terrestrial extent of the Irish Sea Ice Stream (ISIS), which drained a large proportion of the last British–Irish Ice Sheet, impinged on to the Isles of Scilly during Marine Isotope Stage 2. However, the age of this ice limit has been contested and the interpretation that this occurred during the Last Glacial Maximum (LGM) remains controversial. This study reports new ages using optically stimulated luminescence (OSL) dating of outwash sediments at Battery, Tresco (25.5 ± 1.5 ka), and terrestrial cosmogenic nuclide exposure dating of boulders overlying till on Scilly Rock (25.9 ± 1.6 ka), which confirm that the ISIS reached the Isles of Scilly during the LGM. The ages demonstrate this ice advance on to the northern Isles of Scilly occurred at ∼26 ka around the time of increased ice‐rafted debris in the adjacent marine record from the continental margin, which coincided with Heinrich Event 2 at ∼24 ka. OSL dating (19.6 ± 1.5 ka) of the post‐glacial Hell Bay Gravel at Battery suggests there was then an ∼5‐ka delay between primary deposition and aeolian reworking of the glacigenic sediment, during a time when the ISIS ice front was oscillating on and around the Llŷn Peninsula, ∼390 km to the north. Copyright © 2017 The Authors. Journal of Quaternary Science Published by John Wiley & Sons, Ltd.